PENGAKUAN DAN PENGUKURAN PENDAPATAN MENURUT PSAK NO.23 PADA PERUSAHAAN BIRO JASA PERJALANAN - Rinawati, Dwi; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The main problem in accounting income is the recognition and the measurement of revenue. If the revenuerecognition and the measurement of income is inaccurate, then the corporate operating activities will beconsidered to be ineffective and inefficient.The purpose of this research is to find out whether the revenuerecognition and the measurement of income methods which has been implemented by the company is compatiblewith the Statement of Financial Accounting Standards No. 23.Some aspects of the problemswhich are examinedby the authors are about the transaction recording, revenue recognition and the amount of income.The result ofthe research at PT. Megananda Trans shows that the method which has been applied to recognize their revenueis cash basic method in which the revenue is recognized upon the receiving of payment. The revenue recognitionof PT. Megananda Trans should use the basic accrual method in which the revenue is recognized when thetransaction occurs, as it has been determined in the Financial Accounting Standards so the financial statementthat has been presented is reliable. PT. Megananda Trans for the measurement of income has determined theStatement of Financial Accounting Standard No. 23 and it can be seen from the revenue recognition whichismeasured by using the fair value of return that can be accepted or acceptable by the company.Keywords: Revenue recognition, measurement of income,Statement of Financial Accounting Standards No. 23